Moralitas Omnibus Law Undang-Undang Cipta Kerja Dalam Rangka Pemenuhan Kebutuhan Hukum Masyarakat - Delfina Gusman (Nagari Law Review, 2021)
Fulfilling the legal needs of the community is one of the legal materials regulated in Article 10 paragraph 1 of law number 12 of 2011 concerning the formation of statutory regulations. However, there are unclear parameters or characteristics of community law compliance. This has resulted in the emergence of laws that do not meet the legal needs of the community. For example, The Law Of Cipta Kerja. There are many legal problems in this law, both in the process of formation and in substance. When linked with the principles of morality, several articles in this law violate these principles. One of them is moral principle that serve as an ethical foundation in the formation of law, especially the value of justice for all people.